Asymmetric phase anomaly of terajet generated from dielectric cube under oblique illumination; Applied Physics Letters; Vol. 110, iss. 20 - Nguyen Pham Hai Huy; Hisatake Sh. Shintaro; Minin O. V. Oleg Vladilenovich; Nagatsuma T. Tadao; Minin I. V. Igor Vladilenovich (2017, 2017)
Title screen